The Effectiveness of Blanket Warmer, Warm Intravenous Fluids, and Operating Room Temperature Modification in Preventing Perioperative Hypothermia - Purwadadi, I Kadek; Agustini, Ni Luh Putu Inca Buntari; Nuryanto, Kadek; Putri, Ni Made Manik Elisa (Jurnal Kesehatan, 2024)
Hypothermia is a dangerous condition where the body temperature drops drastically (<36°C). If not promptly addressed, it can be life-threatening, with a mortality rate of approximately 21% for moderate hypothermia and 40% for severe hypothermia. This literature review aims to identify the most effective preventive measures to be implemented in the operating room to prevent perioperative hypothermia. This study utilized a literature review method, analyzing articles from two databases, PubMed and Science Direct. After applying relevant keywords, a total of 401 articles were obtained. These articles were then identified, screened, and examined for eligibility, resulting in 12 included articles. Nine articles reported that warm intravenous fluids, warm irrigation fluids, electric warming blankets, warming mattresses, and operating room temperature modifications were significantly beneficial in preventing perioperative hypothermia. In comparison, two articles found no significant benefit in prevention. There needs to be a consensus among the reviewed articles regarding the most effective preventive measures for perioperative hypothermia. Additionally, none of the articles examined the combined use of all three interventions to prevent hypothermia in perioperative patients.